Pelatihan Penggunaan Cerita Pendek dalam Membangun Keterampilan Berfikir Analitis Siswa - Rizka Indahyanti; Ikbal Ikbal; Suci Adriana Nurfadilah; Amina Belatu; Rijal Anugrah (LITERA ABDI: Jurnal Pengabdian Masyarakat, 2025)
This training aims to analyze the influence of the short story process at SMAN 14 Maros on the skills of analyzing every good value that can be learned as well as growing language skills. Reading short stories is an activity that gives students imaginative experiences in opening up analytical thinking skill, helps them understand the dynamics of conflict between characters, and fosters social sensitivity and personality. Apart from that, short stories also function to foster students' social sensitivity through the moral messages contained in the stories, and can enrich their personalities